Battery-operated Independent Radiation Detector Data Report from Exploration Flight Test 1 - Bahadori, Amir A.; Semones, Edward J.; Gaza, Ramona; Kroupa, Martin; Rios, Ryan R.; Stoffle, Nicholas N.; Campbell-Ricketts, Thomas; Pinsky, Lawrence S.; Turecek, Daniel (My University, 2016)
This report summarizes the data acquired by the Battery-operated Independent Radiation Detector (BIRD) during Exploration Flight Test 1 (EFT-1). The BIRD, consisting of two redundant subsystems isolated electronically from the Orion Multi-Purpose Crew Vehicle (MPCV), was developed to fly on the Orion EFT-1 to acquire radiation data throughout the mission. The BIRD subsystems successfully triggered using on-board accelerometers in response to launch accelerations, acquired and archived data through landing, and completed the shut down routine when battery voltage decreased to a specified value. The data acquired are important for understanding the radiation environment within the Orion MPCV during transit through the trapped radiation belts.
Citation: Bahadori AA, Semones EJ, Gaza R, Kroupa M, Rios RR, Stoffle NN, Campbell-Ricketts T, Pinsky LS, and Turecek D 2015 Battery-operated Independent Radiation Detector Data Report from Exploration Flight Test 1 NASA/TP-2015-218575 NASA Johnson Space Center: Houston, TX http://ston.jsc.nasa.gov/collections/TRS/397.refer.html
Keywords: Orion; MPCV; EFT1; BIRD; Radiation